Neutrophil–Lymphocyte Ratio in Fibromyalgia and Axial Spondyloarthritis: A Potential Biomarker for Diagnosis and Disease Activity - Miriam Almirall; Esther Espartal; Xabier Michelena; Carlos Suso-Ribera; Mayte Serrat; Sara Marsal; Alba Erra (Biomedicines, 2025)
Objective: The Neutrophil–Lymphocyte Ratio (NLR) has been proposed as an inflammatory biomarker in several diseases, including Fibromyalgia, with controversial results. The objectives of this study were to: (1) compare NLR values among participants with Fibromyalgia, Axial Spondyloarthritis, and healthy controls; (2) assess the relationship between NLR and disease activity; and (3) establish diagnostic and activity cut-off values. Methods: A total of 112 age and gender-matched participants were included in each group. NLR values were compared between groups, correlations with disease activity were analyzed, and cut-off values were calculated using Receiver Operating Characteristic (ROC) curves. Results: The NLR was significantly higher in Fibromyalgia patients compared with healthy controls (1.8 ± 0.5 vs. 1.4 ± 0.2; p < 0.001) and in Axial Spondyloarthritis patients compared with both Fibromyalgia patients (2.1 ± 0.3 vs. 1.8 ± 0.5; p < 0.001) and healthy controls (2.1 ± 0.3 vs. 1.4 ± 0.2; p < 0.001). Within disease groups, the NLR was also significantly higher in patients with severe Fibromyalgia (FIQ ≥ 59) compared with non-severe cases (1.9 ± 0.5 vs. 1.7 ± 0.4; p = 0.008) and in patients with high/very high Axial Spondyloarthritis activity compared with those with low/inactive disease (2.3 ± 0.3 vs. 1.9 ± 0.2; p < 0.001). ROC analysis identified the NLR cut-off values of 1.54 for Fibromyalgia diagnosis, 1.64 for severe disease, 1.61 for Axial Spondyloarthritis diagnosis and 1.95 for high/very high disease activity. Conclusions: The NLR may serve as a cost-effective, rapid, and accessible biomarker for establishing diagnosis and disease activity in Axial Spondyloarthritis and, to a lesser extent, in Fibromyalgia. Further research is needed to validate these findings and explore NLR’s role alongside other inflammatory markers.